COVERED INTEREST ARBITRAGE UNTUK MENGATASI PERUBAHAN KURS VALAS DI INDONESIA - MARIA MARIA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this study is to do the simulation by using Arbitrage facilities such investment on foreign exchange. This study ·will find the best foreign exchange between US Dollar, Poundsterling and Yen, with the best interest rate and the best inflation rate for such transaction by using Arbitrage transaction mechanism. In foreign exchange transaction, the speculation risk is very high but this is becoming a reason why this kind of transaction being attractive and obviously more economic agents done is business. When the exchange rates become high, economic agents have a chance to get the high profit because of such differences occurred on exchange rates. The problem is how to manage this situation as well as possible mainly for managers. The role of estimation on foreign exchange for example by knowing the variables that determined foreign exchange rates, is important for trading on foreign exchange. Beside that Arbitrage can give an additional profit from such investment in a foreign exchange and windfall profit from spread of the foreign exchange.